Peran Literasi Keuangan, Financial Self Efficacy dan Risk Tolerance terhadap Pengambilan Keputusan Investasi (Studi Masyarakat Dewasa Muda di Provinsi Yogyakarta) - Elizabeth Fiesta Clara Shinta Budiyono (LPPM Universitas Buddhi Dharma, 2024)
Economic growth is one of the parameters used to see the level of success of economic development, which originates from per capita income, quality of life index and human development in a country. One aspect that can support economic growth is by carrying out investment activities. Investment activities continue to be promoted at all levels of society, especially those who are currently young adults. Young adults are those who, in 2024, will belong to 3 generations at once, namely some of the Z generation and the millennial generation. Besides using rational factors in making decisions, investors often behave irrationally in their investment activities. Irrational attitudes are characterized by psychological factors such as self-efficacy and risk tolerance. This research examines the influence of financial literacy, financial self-efficacy and risk tolerance on investment decisions of young adults aged 20-42 years in Yogyakarta Province. The research method used is multiple regression testing using SPSS Ver.25. this research shows a partial or simultaneous influence on financial literacy, self-efficacy and risk tolerance on investment decisions among young adults in Yogyakarta Province. Financial literacy among the people in Yogyakarta should continue to be improved to support increased investment activities. With increasing financial literacy, investor self-efficacy will increase and influence the increase in investment. With these findings, the author provides suggestions, especially for companies operating in the field of investment product services, not only to offer investment products but also to provide education and outreach regarding existing investment assets in order to be able to increase financial literacy, self-efficacy and make it easier for investors to recognize the characteristics of assets that suit their risk tolerance.